Computed tomographic evaluation of the proximity of needles placed for perineural anesthesia of the palmar digital nerves to synovial structures in the foot: an ex vivo study - Gruyaert, Mounia; Oosterlinck, Maarten; Haspeslagh, Maarten; Nagy, Annamaria (Frontiers in Veterinary Science, 2024)
Author contributions: Mounia Gruyaert contributed to the study design, execution, data interpretation and preparation of the manuscript. Maarten Haspeslagh contributed to the data analysis and interpretation. Maarten Oosterlinck and Annamaria Nagy contributed to the study design, data interpretation and preparation of the manuscript. All authors gave their final approval of the manuscript. Mounia Gruyaert takes responsibility for the integrity of the data and the accuracy of the data analysis.Ethical Considerations: Research ethics committee oversight not required by this journal: cadaveric study.The material used was derived from horses that were subject to euthanasia for unrelated reasons. By signing the general consent form of the hospital on admission of all cases, owners agree for data acquired on their horses to be used for teaching and research purposes.